Peran Pendidik dalam Membangun Interaksi Antar Siswa di Sekolah - Tabang, Valentino; Saefulloh, Ahmad (Universitas Palangka Raya, 2023)
In the author's research in the field, it was found that interaction between students in the school environment of SMAK Aloysius is very lacking. This is certainly born from the individualistic attitude of students who are comfortable with themselves and do not want to interact with others. This should certainly be a matter of reflection for educators. That, school is not just a place for educators (teachers) to transfer all their knowledge to students because it will only develop the cognitive aspects of each student and ignore other aspects (affective, psychomotor, conative, social and spiritual) which are no less important than cognitive aspects. Ki Hajar Dewantara's among method is a huge contribution to the advancement of the education process in Indonesia, especially the role or position of a teacher in school. Teachers must be carers for students who are not only concerned with cognitive aspects but also improve other aspects so that they can grow into complete human beings. One of them is helping them to become human beings who care about others who are willing to interact and relate to anyone.